(5s+6)(s-2)=

Simple and best practice solution for (5s+6)(s-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5s+6)(s-2)= equation:


Simplifying
(5s + 6)(s + -2) = 0

Reorder the terms:
(6 + 5s)(s + -2) = 0

Reorder the terms:
(6 + 5s)(-2 + s) = 0

Multiply (6 + 5s) * (-2 + s)
(6(-2 + s) + 5s * (-2 + s)) = 0
((-2 * 6 + s * 6) + 5s * (-2 + s)) = 0
((-12 + 6s) + 5s * (-2 + s)) = 0
(-12 + 6s + (-2 * 5s + s * 5s)) = 0
(-12 + 6s + (-10s + 5s2)) = 0

Combine like terms: 6s + -10s = -4s
(-12 + -4s + 5s2) = 0

Solving
-12 + -4s + 5s2 = 0

Solving for variable 's'.

Factor a trinomial.
(-6 + -5s)(2 + -1s) = 0

Subproblem 1

Set the factor '(-6 + -5s)' equal to zero and attempt to solve: Simplifying -6 + -5s = 0 Solving -6 + -5s = 0 Move all terms containing s to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -5s = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -5s = 0 + 6 -5s = 0 + 6 Combine like terms: 0 + 6 = 6 -5s = 6 Divide each side by '-5'. s = -1.2 Simplifying s = -1.2

Subproblem 2

Set the factor '(2 + -1s)' equal to zero and attempt to solve: Simplifying 2 + -1s = 0 Solving 2 + -1s = 0 Move all terms containing s to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1s = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1s = 0 + -2 -1s = 0 + -2 Combine like terms: 0 + -2 = -2 -1s = -2 Divide each side by '-1'. s = 2 Simplifying s = 2

Solution

s = {-1.2, 2}

See similar equations:

| -7(4-4x)=-168 | | 8(t-2)+6t=7(2t+3)-9 | | -6(-7x-1)-x=-158 | | 7n-15=-16+8n | | -4x-6(-2x+15)=-10 | | 1/2(4/3)(3.14)(2.5)^3 | | -2x-3=2x+9 | | 4(6n-7)=140 | | 3(x-1)=7+5 | | n^2+9=34 | | Y=29(3)x | | 4(6n-7)=40 | | Y=29(3) | | 2/3x12/11 | | (n-6)(n-4)= | | 2j-12=2 | | -5.7=1.9+1.9z | | 4n-3=29+8n | | 2x-52=88 | | 8x-11+15x+3x+9=180 | | -5x-4(-x-17)=76 | | y+7=7(x-2) | | -10(b+645)=-490 | | 15-1/2b= | | 4w-60=440 | | 2g-17=1 | | y-6=6(x+6) | | 7xc=-3 | | 8x-1+15x+3x+9=360 | | Z+5=5 | | 5x+7(-x-14)=-88 | | 13x-30=9 |

Equations solver categories